A Stackelberg Game Theoretic Approach for Optimal Electricity Pricing Dynamics employing Time-of-Use Algorithm - Koonamparampath, J.; Sawant, M.; Atharva, K.; Sheikh, A. (International Conference on Control, Decision and Information Technologies (Online), 2019)
Efficient utilization of resources is required in many scenarios which are facilitated by appropriate decision processes. For a problem requiring satisfaction of multiple objectives by different agents in a complex system, game theory helps to resolve such issues. Exploiting the structure of a model presents various avenues to implement games signifying the impact of the topology of the network. In hierarchical structures, there are established designations of leaders and followers among the agents. For the electricity pricing market, the noted players are the Utility Companies (UCs) and the users. A Stackelberg game theoretic approach is implemented in the market to find an equilibrium between the UCs and the users. The UCs prefer to keep the user load consumption profile as close to the nominal demand. The goal is to accomplish an equilibrium via stimulus to regulate user behaviour i.e. user load profile, through Time-of-Use (ToU) pricing. The negotiation of load consumption and the quoted price fits within the mould of the leader-follower game. The paper shows that both parties benefit through the Time-of-Use pricing algorithm while providing an optimal response to each other's actions.